Prevalence of extended-spectrum beta-lactamase-producing Enterobacteriaceae among clinical isolates in Turaif general hospital, northern borders- Saudi Arabia - El-Masry, Eman A; Alruwaili, Faisal Mansour; Taha, Ahmed E; Saad, Abeer E; Taher, Ibrahim A (The Journal of Infection in Developing Countries, 2023)
Introduction: Enterobacteriaceae that produce extended-spectrum beta-lactamase (ESBL) are quickly spreading, posing a threat to world healthcare. Methodology: 138 gram-negative bacteria were collected from different samples (stool, urine, wound, blood, tracheal aspirate, catheter tip, vaginal swab, sputum, and tracheal aspirate) from hospitalized patients. Samples were subcultured and identified in accordance with their biochemical reactions and culture characteristics. Against all the isolated Enterobacteriaceae, an antimicrobial susceptibility test was performed. VITEK®2 system, phenotypic confirmation, and Double-Disk Synergy Test (DDST) had been utilized to identify the ESBLs. Results: Of the 138 samples studied, the prevalence of ESBL-producing infections among the clinical samples of the present study was 26.8 % (n = 37). E. coli was the commonest ESΒL producer at 51.4% (n = 19) followed by K. pneumoniae at 27% (n = 10). The potential risk factors for the ESBL development that produces bacteria were as follows, patients with the presence of indwelling devices, previous history of hospital admission, and usage of antibiotics. ESBL is statistically (p ≤ 0.05) higher among the patients with indwelling devices, ICU admission, who had a previous hospital admission in the last 6 months as well as who was given antibiotics (quinolones and/or cephalosporins) in the last 6 months. One hundred thirty-two (95.7%) of ESBL isolates were resistant to amoxicillin, while the lowest resistance was for fosfomycin (15.2%). Conclusions: ESBL-producing Enterobacteriaceae are highly prevalent in Turaif General Hospital setting with some potential risk factors. A strict policy to be made available on the usage of antimicrobials in hospitals and clinics should be established.